An experimental study of the biological impact of a superflare on the TRAPPIST-1 planets - Abrevaya, Ximena Celeste (2024)
In this study, we conducted experiments to assess the biological effects of high fluences of UV radiation (UVR) on the TRAPPIST-1 planetary system (planets e, f, g within the habitable zone), unlike previous estimates made by other authors which used theoretical approaches. To this end, we first calculated the UV fluxes at the orbits of the planets of the TRAPPIST-1 system during quiescent conditions and during a superflare. We then studied the effects of UVR on microbial life by exposing UV-tolerant (Deinococcus radiodurans) and UV-susceptible bacteria (Escherichia coli) to fluences equivalent to a superflare on the unshielded surface of these planets. Based on the results of our laboratory experiments, we have found a survival fraction of for D. radiodurans and a survival fraction below the limit of detection for E. coli at the surface of the planet e, which would receive the highest UVR flux. These survival fractions were higher for the planets f and g. In contrast to the results obtained by other authors which used theoretical estimates, we show that a fraction of the population of microorganisms could tolerate the high UVR fluences of a superflare on the surface of TRAPPIST-1 planets, even without any shielding such as that provided by an atmosphere or an ocean. Our study evidences the existence of methodological problems in theoretical approaches. It also emphasizes the importance of performing specifically designed biological experiments to predict microbial survival in extraterrestrial contexts.